Observation of first and third harmonic responses in two-dimensional AlGaAs/GaAs HEMT devices due to plasma wave interaction - Hashima, Abdul Manaf; Kasai , Seiya; Hasegawa, Hideki (Elsevier Ltd, 2008)
Plasma waves are oscillations of electron density in time and space, and in deep submicron field effect transistors, typical plasma frequencies, !p, lie in the terahertz (THz) range and do not involve any quantum transitions. Hence, using plasma wave excitation for detection and/or generation of THz oscillations is a very promising approach. In this paper, the investigation of plasma wave interaction between the plasma waves propagating in a short-channel High-Electron-Mobility Transistor (HEMT) and the radiated electromagnetic waves was carried out. Experimentally,we have demonstrated the detection of the terahertz (THz)radiation by an AlGaAs/GaAs HEMT up to third harmonic at room temperature and their resonant responses show very good agreement with the calculated results.